Web-Based Application for Sales of Water Depot Accessories and Equipment at VQ Air Store - Adawiah, Sania; Sudrajat, Adjat; Fauka, Ahfi; Parghani, Rizal (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
An online shop website refers to a website that is equipped with an e-commerce system, allowing users to engage in transactions. In addition to the requirement of loading product offerings, the website must also possess inventory management capabilities, automated shipping cost estimates, and support for manual and automated payments using a Payment Gateway.This research aims to develop an application that facilitates the sale of accessories and supplies required for a gallon of drinking water depot at the VQ WATER store. This application will be directly linked to the website and provide comprehensive information about the VQ Water Depot Gallon Shop, including prices and purchasing instructions. The aim is to enhance user convenience when locating depot equipment. The research methodology employed in this final project is the Waterfall approach, which incorporates UML modeling. The attained outcomes manifest as an internet-based sales application accessible through a website, facilitating the exploration of depot equipment requirements. The final project entails the development of a website-based online sales application that facilitates the convenient purchase of gallon depot products. This application provides users with visual representations of accessories and equipment, their respective costs and purchasing instructions.